Analisis Pengakuan, Pengukuran, Penyajian, Dan Pengungkapan Persediaan Bahan Baku (Studi Kasus Pabrik Super Jaya Kelurahan Wolomarang) - Novira, Patresia Delvin Anggreani; Mitan , Wilhelmina; Jaeng , Wihelmina M.Yulia (Universitas Nusa Nipa Maumere, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in Indonesia’s economy. However, most business actors have not fully implemented proper inventory accounting in accordance with standards. This study aims to analyze the recognition, measurement, presentation, and disclosure of raw material inventories at Pabrik Super Jaya and evaluate their compliance with the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM). This research employed a qualitative descriptive method with primary data obtained through observation, interviews, and documentation. The results indicate that inventory recognition is still manual, using notebooks without formal evidence. Measurement is based on raw material costs, labor, and daily expenses, without formal methods such as FIFO or average. Financial reporting is limited to a simple income statement without detailed inventory or notes to financial statements. Disclosure is limited to physical quantities and nominal values. Thus, Pabrik Super Jaya’s inventory practices are not fully aligned with SAK EMKM standards